Features and Prospects of Industry 4.0 in the Agrarian Sector of Ukraine in Wartime: Economic and Accounting Aspects - Liudmyla Chip; Natalia Kantsedal; Olena Kopishynska; Yuri Utkin; Olena Taran-Lala (Engineering Proceedings, 2023)
The agrarian sector of Ukraine is an integral part of the country’s economy [...]